2016
DOI: 10.1007/s12517-015-2106-y
|View full text |Cite
|
Sign up to set email alerts
|

Runoff response to the glacier shrinkage in the Karatal river basin, Kazakhstan

Abstract: The fresh water lack in Central Asian countries with fast-growing population is one of the most critical problems in this region, where runoff of most rivers closely depends on supply of glaciers melting water. However, the impact of glacier shrinkage on the river runoff remains poorly understood. In this paper, we took the Karatal river basin, Tien Shan, as a model for investigation interrelation between dramatic decreasing of glaciers (−1 % annually) and river runoff. We investigated long-term observed clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…These may imply an early snowmelt and early arrival of spring peak runoff along with the global warming and the state of high variability in temperature of the Tianshan Mountains. Changes of runoff and peaks moving forward are already detected in Central Asian rivers that are mainly supplied by glacier and snowmelt water from Tianshan Mountains [49][50][51]. Changes in SCA may also change the future runoff regimes and water availability in high-altitude catchments [55], thus impacting ecosystem, irrigation and agriculture, and water resources in the densely populated downstream areas [16,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These may imply an early snowmelt and early arrival of spring peak runoff along with the global warming and the state of high variability in temperature of the Tianshan Mountains. Changes of runoff and peaks moving forward are already detected in Central Asian rivers that are mainly supplied by glacier and snowmelt water from Tianshan Mountains [49][50][51]. Changes in SCA may also change the future runoff regimes and water availability in high-altitude catchments [55], thus impacting ecosystem, irrigation and agriculture, and water resources in the densely populated downstream areas [16,26].…”
Section: Discussionmentioning
confidence: 99%
“…The climate characteristics and cryosphere change showed obvious differences in these four subregions [10,13,20]. The total area of the study area is 135.5 × 10 4 km 2 ; and the areas of these subregions are accounted for 13.9% (Central Tianshan), 34 increased the runoff in the Tianshan Mountains due to the accelerated glacier/snowmelt [44,[49][50][51]. Therefore, it is very necessary to examine the possible linkages between the snow cover and the climatic parameters (precipitation and temperature) in the Tianshan Mountains.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the mismatch between decreasing trends in snow indicators and the increasing river runoff could be the result of enhanced glacier melting. Heavily glacierized river basins showed mainly positive runoff trends in the past few decades (simulated under different scenarios in the head rivers of the Tarim River basin), while those with less or no glacierization exhibited wide variations in runoff Kaldybayev et al, 2016).…”
Section: Current and Future Runoff Changesmentioning
confidence: 99%
“…Moreover, the higher the glacierization of a catchment, the greater was the increment in runoff (Duethmann et al, ; Kaldybayev et al, ). Another example is the Aksu River, which originates in the southern flank of the Tienshan Mountains and is the largest headwater of the Tarim River Basin (providing 74% of water to the mainstream).…”
Section: Resultsmentioning
confidence: 99%